In vivo anti-ulcerogenic effect of okra (Abelmoschus esculentus) on ethanol-induced acute gastric mucosal lesions - Ortac, Deniz; Cemek, Mustafa; Karaca, Turan; Buyukokuroglu, Mehmet E.; Ozdemir, Zafer O.; Kocaman, Ayse Tuba; Gones, Sadik (TAYLOR & FRANCIS LTD, 2018)
Context: Okra, Abelmoschus esculentus (L.) (Malvaceae), is a medicinal plant widely used in Turkish traditional medicine for the treatment of various diseases such as ulcers and gastritis. Objective: In the present study, we evaluated the gastroprotective effect of okra against ethanol-induced acute gastric mucosal injury in animal models. Materials and methods: Wistar rats were treated with 500, 250 or 100 mg/kg okra; 20 mg/kg famotidine (Fam); and 75 mg/kg quercetin (Que). Following a 60 min period, all the rats were given 1 mL of ethanol (80%). One hour after the administration of ethanol, all groups were sacrificed. Results: At 5000 mg/kg, the extract produced (okra) no signs of toxicity in animals. Okra 500, 250, 100, Fam 20 and Que 75 inhibited ulcer formation by 81.0, 67.5, 67.0, 76.3 and 72.4%, respectively. Okra 500 significantly decreased edema, hemorrhage and inflammation scores compared with the ethanol group (p < 0.05). The oxidant levels decreased significantly in the all study groups compared within ethanol group (p < 0.001). Serum beta-carotene and retinol levels significantly increased 40.2 and 45.4% in the okra 500 group. In okra 500, 250 and Fam 20 groups, apoptosis significantly decreased (p < 0.001), while okra 500, 250 and Fam 20 groups showed a higher percentage of cell proliferation compared with the ethanol group (p < 0.001). Discussion and conclusions: Our in vivo data indicate that okra has a gastroprotective effect against ethanol and could reduce the gastric ulcer as seen from biochemical and histopathological results. We suggest that okra could be a possible therapeutic antiulcer agent.
Keywords: Gastroprotection; apoptosis; gastric ulcer; immunohistochemistry; ulcer index; ulcer inhibition; NITRIC-OXIDE; ASCORBIC-ACID; RATS; GLUTATHIONE; INJURY; ANTIOXIDANT; QUERCETIN; EXPRESSION; DAMAGE; OIL; Plant Sciences; Medical Laboratory Technology; Pharmacology & Pharmacy